Elucidating the role of interfacial MoS2 layer in Cu2ZnSnS4 thin film solar cells by numerical analysis. (15th January 2019) - Ferdaous, M.T.; Shahahmadi, S.A.; Chelvanathan, P.; Akhtaruzzaman, Md.; Alharbi, F.H.; Sopian, K.; Tiong, S.K.; Amin, N.
Highlights: Effect of MoS2 interfacial layer between CZTS and Mo back contact is studied. Simulation wxAMPS-1D is used by varying electronic parameters of p and n-MoS2 . CZTS device underperforms without any MoS2 due to high back contact barrier. Transition in efficiency is noticed when carrier concentration exceeds 10 16 cm −3 . MoS2 with lower affinity and band gap is ideal to induce desirable band alignment. Abstract: In this study, the effects of transition metal dichalcogenide, MoS2 interfacial layer formation between the Cu2 ZnSnS4 (CZTS) absorber layer and Mo back contact in a conventional CZTS thin film solar cell (TFSC) structure have been studied by numerical simulation using wxAMPS-1D software. The goal of this study is to elucidate the effects of both n and p-type MoS2 on the overall CZTS solar cell's performance from the viewpoint of metal-semiconductor junction and heterojunction band alignment. Interestingly, CZTS device, regardless of p or n-type MoS2 largely outperforms device without any MoS2 due to lower back contact barrier value. Significant transition in efficiency is noticed when acceptor (increases efficiency) or donor (decreases efficiency) concentration has a transition from 10 16 cm −3 to higher concentration of 10 18 cm −3 or more. Also, effect of variable electron affinity and band gap of MoS2 has been discussed from band alignment perspective. Generally, MoS2 layer with lower electron affinity and band gap is preferred to induce desirable band alignment and subsequently result in higher efficiency. All-in all, the formation of p-type MoS2 in CZTS solar cells can be tuned to improve the cell performance mainly by doping with higher acceptor doping concentration and limiting layer thickness. However, the detrimental effect of n-MoS2 can be prevented by maintaining thinner layer in the vicinity of ∼30 nm with low to moderate donor doping (<10 16 cm −3 ).